Assessing the Effectiveness of Sci-Bono Discovery Centre: A Comparative Analysis with Other Science Centres in the SADC Region - Mfanelo Ntsobi; Blondel Nyamkure; Bongani June Mwale (New Advances in Business, Management and Economics Vol. 3, 2025)
Science centres play a vital role in igniting scientific curiosity, fostering literacy, and promoting innovation across the Southern African Development Community’s (SADC) region. This report benchmarks SADC science centres, focusing on their strengths, weaknesses, opportunities, and threats (SWOT analyses). It offers a comparative overview of existing facilities while identifying opportunities for collaboration and development to empower the region through science and technology. South Africa leads with well-established centres like the Sci-Bono Discovery Centre, which provides interactive exhibits, science education programs, and public engagement initiatives in science, technology, engineering, and mathematics (STEM). Other SADC countries, while often emphasizing research through universities and institutes, show a growing interest in establishing dedicated science centres. The diverse landscape of scientific centres across the region underscores the need for collaborative efforts to drive innovation and capacity building in science and technology. This analysis is based on desk research and includes recommendations for further direct engagement with science centres to obtain more comprehensive insights.